Analisis Transmisi Nilai Tukar Rupiah terhadap Inflasi di Indonesia: Studi Kepustakaan 2015–2024 (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Global economic uncertainty and exchange rate fluctuations pose significant challenges to monetary stability in Indonesia, particularly in maintaining a controlled inflation rate. This study aims to analyze the transmission mechanism of the rupiah exchange rate to the inflation rate in Indonesia from 2015 to 2024. The method used in this study is library research by collecting, reviewing, and synthesizing data from various scientific literature, official central bank reports, and related journal articles published over the past decade. The research findings indicate that rupiah depreciation has a significant influence on rising inflation through the imported inflation channel, where currency depreciation increases the cost of raw materials for industries dependent on foreign markets. Furthermore, the findings reveal that the effectiveness of this transmission is influenced by public expectations and monetary policy taken by Bank Indonesia through adjustments to the benchmark interest rate. The implications of this study emphasize the importance of synergy between a stable exchange rate policy and controlling the supply of domestic goods to minimize the impact of external shocks on public purchasing power. The government and monetary authorities are advised to continue strengthening foreign exchange reserves and encouraging the use of local currencies in international transactions to reduce dependence on the United States dollar and maintain national price stability.